2017
DOI: 10.3389/fpsyt.2017.00127
|View full text |Cite
|
Sign up to set email alerts
|

A New Division of Schizophrenia Revealed Expanded Bilateral Brain Structural Abnormalities of the Association Cortices

Abstract: The phenomenological and, consequently, pathophysiological heterogeneity of schizophrenia may be substantially decreased by determining etiologically valid subgroups. In a cross-sectional study, we analyzed the brain structural impairments of outpatients with schizophrenia using concurrent subgrouping methods, partly to enhance the extensity of exploration, and partly to estimate the validation of the divisions. High resolution T1-weighted MR images were obtained for 21 patients and 13 healthy controls. Locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Many studies have reported abnormalities in the insula which were related to negative symptoms in schizophrenia ( 17 , 65 ). These are in accordance with findings that a volumetric decrease of the insula relative to controls could be detected in schizophrenia with PNS ( 66 , 67 ). Similarly, structural abnormalities in the left amygdala were found to be significantly associated with PANSS negative symptoms ( 68 ), which is consistent with studies that found a negative correlation between the volume of the hippocampus-amygdala complex and clinical ratings of negative symptoms and thought disturbances ( 69 , 70 ).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have reported abnormalities in the insula which were related to negative symptoms in schizophrenia ( 17 , 65 ). These are in accordance with findings that a volumetric decrease of the insula relative to controls could be detected in schizophrenia with PNS ( 66 , 67 ). Similarly, structural abnormalities in the left amygdala were found to be significantly associated with PANSS negative symptoms ( 68 ), which is consistent with studies that found a negative correlation between the volume of the hippocampus-amygdala complex and clinical ratings of negative symptoms and thought disturbances ( 69 , 70 ).…”
Section: Discussionsupporting
confidence: 93%
“…Volumetric MRI studies of cerebellum and vermis in schizophrenic patients showed greater volume of vermis volume than control group, which reveal significant correlation with positive symptoms severity, thought disorder and verbal logical memory impairment. Also results revealed more cerebellar hemispheric volume asymmetry in schizophrenic patients [3] .…”
Section: Introductionmentioning
confidence: 75%
“…More detailed information on each of the included studies is shown in Tables 1, 2. For the VBM-meta-analysis, we identified 15 experiments with the DMN (Paillère-Martinot et al, 2001;Sigmundsson et al, 2001;Salgado-Pineda et al, 2004;Jayakumar et al, 2005;Bassitt et al, 2007;Koutsouleris et al, 2008;Meisenzahl et al, 2008;Herold et al, 2009;Whitford et al, 2009;Huang et al, 2015;Poletti et al, 2016;Kuroki et al, 2017;Szendi et al, 2017;Spalthoff et al, 2018;Neugebauer et al, 2019), 5 experiments with the CEN (Jayakumar et al, 2005;Bassitt et al, 2007;Koutsouleris et al, 2008;Meisenzahl et al, 2008;Herold et al, 2009), and 15 experiments with the SN (Paillère-Martinot et al, 2001;Sigmundsson et al, 2001;Salgado-Pineda et al, 2004;Jayakumar et al, 2005;Bassitt et al, 2007;Koutsouleris et al, 2008;Meisenzahl et al, 2008;Herold et al, 2009;Anderson et al, 2015;Poletti et al, 2016;Kim et al, 2017;Kuroki et al, 2017;Szendi et al, 2017;Spalthoff et al, 2018;Neugebauer et al, 2019). For the FC-meta-analysis, we identified 17 experiments with the DMN (Bluhm et al, 2007;Wolf et al, 2011;Fan et al, 2013;…”
Section: Search Resultsmentioning
confidence: 99%
“…Negative symptoms include blunted affect, anhedonia, alogia, avolition, and a sociality (Kirkpatrick et al, 2006;Buchanan, 2007). Negative symptoms recently have been mainly divided into the following two subtypes (Szendi et al, 2017). One is deficit syndrome, which refers to primary or idiopathic persistent negative symptoms.…”
Section: Introductionmentioning
confidence: 99%